The UK Conservative Party Foreign Policy From David CAMERON to Rishi SUNAK - BOUTERA, Aya; KHELEF, Imane (جامعة الوادي - University of Eloued, 2023)
This study aims at investigating the United Kingdom’s Conservative Party’s foreign policy, from David Cameron to Rishi Sunak. To reach the objective of this research, three hypotheses have been formulated. The first hypothesized that the differences and similarities between the Conservative Party leaders might be clear througnout the economic, social, and political issues they dealt with. The second hypothesis showed that the different leaders’ foreign policies may have different economic, political, and diplomatic effects on the United Kingdom. The hypothesis presumes that the different conservative party policies may impact the United Kingdom’s foreign policy, especially with the United States, European Union, and the Middle East. The study's results demonstrate that David Cameron's foreign policy exerted significant emphasis on the pursuit of economic diplomacy, global engagement, and international cooperation. In contradistinction, the foreign policy of the actual Prime minister Rishi Sunak is characterized by a focus on national security, an enhancement of bilateral relationships, and a proclivity towards a more assertive stance in global affairs. Nonetheless, certain instances of continuity exist, signifying mutual ideological outlooks within the party تهدف هذه الدراسة إلى التحقيق في السياسة الخارجية لحزب المحافظين البريطاني ، من ديفيد كاميرون إلى ريشي سوناك. للوصول إلى الهدف من هذا البحث ، تمت صياغة ثلاث فرضيات. افترضت الفرضية الأولى أن الاختلافات والتشابهات بين قادة حزب المحافظين قد تكون واضحة من خلال القضايا الاقتصادية والاجتماعية والسياسية التي تعاملوا معها. أظهرت الفرضية الثانية أن السياسات الخارجية للقادة المختلفين قد يكون لها تأثيرات اقتصادية وسياسية ودبلوماسية مختلفة على المملكة المتحدة. تفترض الفرضية أن سياسات الحزب المحافظ المختلفة قد تؤثر على السياسة الخارجية للمملكة المتحدة ، خاصة مع الولايات المتحدة والاتحاد الأوروبي والشرق الأوسط. تظهر نتائج الدراسة أن السياسة الخارجية لديفيد كاميرون قد ركزت بشكل كبير على السعي وراء الدبلوماسية الاقتصادية والمشاركة العالمية والتعاون الدولي. على النقيض من ذلك ، تتميز السياسة الخارجية لرئيس الوزراء الفعلي ريشي سوناك بالتركيز على الأمن القومي ، وتعزيز العلاقات الثنائية ، والميل نحو موقف أكثر حزما في الشؤون العالمية. ومع ذلك ، توجد حالات معينة من الاستمرارية ، مما يدل على وجهات نظر أيديولوجية متبادلة داخل الحزب.
Master’s Degree in Literature and Civilization
Keywords: Conservative Party, David Cameron, Foreign Policy, Rishi Sunak, The United Kingdom; حزب المحافظين ، ديفيد كاميرون ، فورين بوليسي ، ريشي سوناك ، المملكة المتحدة